Somatic alpha‐synuclein mutations in Parkinson's disease: Hypothesis and preliminary data. Issue 6 (14th May 2013) - Proukakis, Christos; Houlden, Henry; Schapira, Anthony H.
ABSTRACT Alpha‐synuclein (SNCA) is crucial in the pathogenesis of Parkinson's disease (PD), yet mutations in the SNCA gene are rare. Evidence for somatic genetic variation in normal humans, also involving the brain, is increasing, but its role in disease is unknown. Somatic SNCA mutations, arising in early development and leading to mosaicism, could contribute to PD pathogenesis and yet be absent or undetectable in DNA derived from peripheral lymphocytes. Such mutations could underlie the widespread pathology in PD, with the precise clinical outcome dependent on their type and the timing and location of their occurrence. We recently reported a novel SNCA mutation (c.150T>G, p.H50Q) in PD brain‐derived DNA. To determine if there was mosaicism for this, a PCR and cloning strategy was used to take advantage of a nearby heterozygous intronic polymorphism. No evidence of mosaicism was found. High‐resolution melting curve analysis of SNCA coding exons, which was shown to be sensitive enough to detect low proportions of 2 known mutations, did not reveal any further mutations in DNA from 28 PD brain‐derived samples. We outline the grounds that make the somatic SNCA mutation hypothesis consistent with genetic, embryological, and pathological data. Further studies of brain‐derived DNA are warranted and should include DNA from multiple regions and methods for detecting other types of genomic variation. © 2013 Movement Disorder Society